Taming the Energy Rise of the Total Proton-Proton Cross-Section - Sergey Ostapchenko; Marcus Bleicher (Universe, 2019)
Steep rise of parton densities in the limit of small parton momentum fraction x poses a challenge for describing the observed energy-dependence of the total and inelastic proton-proton cross sections <semantics> <msubsup> σ p p tot / inel </msubsup> </semantics> : considering a realistic parton spatial distribution, one obtains a too-strong increase of <semantics> <msubsup> σ p p tot / inel </msubsup> </semantics> in the limit of very high energies. We discuss various mechanisms which allow one to tame such a rise, paying special attention to the role of parton-parton correlations. In addition, we investigate a potential impact on model predictions for <semantics> <msubsup> σ p p tot</msubsup></semantics>, related to dynamical higher twist corrections to parton-production processes.